Improving Campus Security with Web-Based Motorcycle Parking Information System using Personal Extreme Programming Method - Wulandari, Sagita; Widiartha, Ida Bagus Ketut; Afwani, Royana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In this modern era, motorcycles are a primary means of transportation used by many people in Indonesian society, including students who use them to access campus. However, the increase in motorcycles also raises safety issues and the availability of parking spaces on campus. The parking system needs to be improved at the Faculty of Engineering, University of Mataram, because it does not use an automatic checking system, resulting in concerns about vehicle safety. This research aims to build a Web-based Motorcycle Parking Information System to store real-time rider data and detect faces and police numbers through CCTV. The Personal Extreme Programming (PXP) method is used as a development method because of its high level of flexibility and its ability to adapt to changing needs. This system was developed using the Bootstrap framework for the front end and Laravel for the back end, with MySQL Workbench as a server to manage the database. System testing uses the Black Box Testing method to ensure each unit or module functions according to predetermined needs. The test results show that all features function validly and by the expected specifications. This research provides an effective solution for improving parking security and parking space management on campus, thus providing a sense of comfort and security for students and all parking users at the Faculty of Engineering, University of Mataram.